Engineering properties of the Bukit Timah Granitic residual soil in Singapore - Zhang, W. G. (2019)
Extensive site investigations were conducted prior to the construction of a Mass Rapid Transit project in Singapore that was predominantly in the Bukit Timah Granite (BTG) formation residual soil. This paper evaluates the engineering properties of the BTG formation residual soil based on data from 208 site investigation boreholes from four different sites. Based on the results from 2481 conventional laboratory tests and 1192 in-situ tests, this paper summarizes the engineering properties of the highly variable BTG residual soil, including conventional composition analysis, index and hydraulic properties, and strength and deformation parameters required for geotechnical analysis and design. Based on these results, the BTG formation is found to be quite heterogeneous. As the degree of weathering decreases with depth from the top of the formation, the BTG residual soil becomes sandier, with reduced silt and clay fractions. The coefficient of permeability and the compression index of the BTG residual soil vary significantly. In addition, the empirical equations relating the shear strength (index) to the standard penetration test (SPT)-N, as well as the equations and charts for determining stiffness, are proposed. These findings, together with the proposed equations or charts, can be used for design guidance of similar projects related to granitic residual soils in Singapore.